Senator : a profile of Bill Bradley in the U.S. Senate - Jaspersohn, William (San Diego : Harcourt Brace Jovanovich, 1992)
Text and photographs reveal the background and day-to-day life of Senator Bill Bradley, both on Capitol Hill and among his constituents in New Jersey.
Includes bibliographical references (p. 201-202) and index.
Keywords: Bradley, Bill, -- 1943- -- Juvenile literature; Bradley, Bill, -- 1943-; United States. -- Congress. -- Senate -- Biography -- Juvenile literature; Legislators -- United States -- Biography -- Juvenile literature; Legislators